Exploring service learning in redesigning and implementing education economics curriculum: experience of university students (2022)
This study examined service learning as an effective strategy for implementation of the Economics curriculum for result-oriented university education. The study was guided by two research questions, adopted a qualitative research approach and utilised phenomenology design. A purposive sampling technique was used to select all students from the departments of Educational Management, Arts and Social Sciences Education, Adult Education, Guidance and Counselling Education, and Special Education who had taken Economics Methods. The reason for the selection of the students was that they had participated in service learning and would be able to provide answers to the research questions. Focus group discussion and key informant interview guides were used to collect data from the participants. The ATLAS. Qualitative software package was used to analyse the data. The findings of the study revealed that service learning was an effective strategy for preparing pre-service teachers for the world of work as it gives undergraduates an opportunity to get involved in communal services such as tutoring, advocacy, and environmental sustainability, among others. It also enhances students’ employability skills, such as financial literacy, project management, teamwork, and resourcefulness. It was therefore recommended that service learning should be infused into the teacher education curriculum for effective implementation of the economics curriculum and to promote undergraduate employability skills.